The Model of Employee Work Productivity - Husainah, Nazifah (Green Publisher, 2023)
The objective of this research is to examine the impact of organizational culture, employee compensation, and work competence on the commitment of employees at the managerial level in various manufacturing companies within the production division in the Special Capital Region of Jakarta. This analysis encompasses both partial and simultaneous effects on employee work productivity. In this study, descriptive and verification methods were employed to examine the managerial level employees in the production division of manufacturing companies located in Jakarta Province. The population consisted of 1,183 employees, while a sample size of 300 respondents was selected. To assess the validity and reliability of the data, a subset of 30 respondents was used. The data collected was qualitative in nature but measured quantitatively through the use of analytical techniques with SPSS and SEM. The findings of this study suggest that in order to cultivate a robust sense of organizational commitment among top management, it is crucial to prioritize the development of work competence. Specifically, focusing on enhancing behavior competence is essential. Additionally, to enhance work productivity, it is imperative to acknowledge the significance of organizational culture. Specifically, placing emphasis on the dimension of outcome orientation is vital.